First Day Cover commemorating United Nations efforts for the cessation of nuclear testing and preservation of humanity - Fleetwood (1964)
Cachet and stamp depict a mushroom cloud from a nuclear weapons test. Cachet was created by Fleetwood and the stamp was commissioned by the United Nations Postal Administration. Postmark depicts the United Nations building.
Keywords: Postage stamps; Nuclear weapons--Testing; Postmarks; Commemorative postage stamps; United Nations; Science on postage stamps; Nuclear nonproliferation; Cachets (Philately); First day covers (Philately)